DECOLONIZING BIOLOGY CLASSROOMS IN NIGERIA: THE SIGNIFICANCE OF CULTURO-TECHNO-CONTEXTUAL APPROACH - Adam, Umar Ayotunde; Adeyemi, Aladesuyi David; Lameed, Soladoye Nurudeen; Gafar, Mustapha Abiodun; Joy, Abolaji Toyin (Erudio Journal of Educational Innovation, 2024)
The methods employed in science instruction are experiencing a transformation, with novel approaches like the Culturo-Techno-Contextual Approach (CTCA) emerging as more efficacious variant. This study explored the efficacy of CTCA in improving the achievement of secondary school students in biology. The study employed an explanatory sequential design. The quantitative phase was quasi-experimental, while the qualitative phase was an in-depth interview. A total of 103 senior secondary II students (the equivalent of grade 11) from two purposively selected schools in Lagos State education district V were sampled. The Achievement Test in Tissue and supporting system which had reliability coefficients of 0.8, were the instruments used to collect quantitative data, while the students’ perception about CTCA interview guide was used to collect the qualitative data. Both groups had a pretest and posttest using the achievement test; treatment lasted four weeks. Data gathered in the survey were analyzed using ANCOVA since intact classes were used. The result obtained showed that the experimental group (mean for experimental = 10.53; control 6.83; F (1, 100) = 34.42; p < 0.05) outperformed the control group. Therefore, the study concluded that CTCA is a potent approach for improving students’ achievement in biology. It was recommended that the use of CTCA should be adopted by biology teachers in secondary schools to enhance learning.